The Perceived Utility and University Enrolment Intention in Indonesia: Students Perspective - Juhaidi, Ahmad; Ma'ruf, Hidayat; Tajudin, Anas; Fitri, Salafuddin; Hamdani, Hamdani (IAIN Ponorogo, 2023)
This study investigates the difference between the utility of general higher education (GHE) and Islamic higher education (IHE), students' enrolment intention, and their correlation. Data were collected using questionnaires. The participants of this study were 753 students in South Kalimantan, Indonesia. Researchers used convenience and snowballing sampling techniques. Data analysis used the Wilcoxon Signed Rank Test and Spearman's correlation. This study proves that the level of utility and all its factors (economic and non-economic benefit, probability of success, and cost) differ significantly between GHE and IHE (Sig<0.05). Moreover, it was found that all factors correlate with enrolment intention (Sig<0.05). However, correlation coefficients indicate that the cost of GHE and IHE is the factor with the weakest correlation (p=0,139 and p=0.084) with enrolment intention. The strongest correlation with enrolment intention is the utility of GHE and IHE (p=0,597 and p=0.579) and the possibility of success in GHE and IHE(p=0,614 and p=0.530). This study offers practical recommendations for higher education institutions and suggests future research.